TRANSFORMASI PERADILAN AGAMA DALAM MERESPONS ISU PERKAWINAN BEDA AGAMA PASCA SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 - Agung Hidayat, Rezky; Flemmig Arwana Tampubolon, Amsal; Krismen, Yudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Interfaith marriages in Indonesia have long been a complex legal issue, given that existing regulations neither explicitly prohibit nor permit them. This legal vacuum has prompted some parties to seek loopholes through court rulings, whether through Religious Courts or District Courts. The issuance of Supreme Court Circular Letter (SEMA) No. 2 of 2023 marks the highest institutional response within the Indonesian judicial system to this issue. This study aims to analyze three aspects: the legal standing of SEMA No. 2 of 2023 within Indonesia’s religious court system; its legal implications for the jurisdiction of Religious Courts in interfaith marriage cases; and the perspective of legal certainty regarding the transformation of the religious court system following the issuance of this SEMA. This study employs a normative legal research method using a statutory approach and a conceptual approach. The results of the study indicate that SEMA No. 2 of 2023 strengthens the position of the Religious Court as a bastion of Islamic legal values, reaffirms the prohibition on the registration of interfaith marriages, and marks a significant institutional transformation, although it still leaves gaps in legal certainty regarding the hierarchy of legislation.